2010
DOI: 10.1002/med.20175
|View full text |Cite
|
Sign up to set email alerts
|

New insights into small‐molecule inhibitors of Bcr‐Abl

Abstract: Chronic myelogenous leukemia (CML) is a myeloproliferative disease associated with a defined genetic abnormality, the Bcr-Abl fusion gene on the Philadelphia chromosome that expresses the constitutively activated tyrosine kinase (TK) Bcr-Abl. This enzyme leads to the malignant transformation of primitive hematopoietic cells and to the consequent disease. The central role of Bcr-Abl in the pathogenesis of CML culminated in the discovery of imatinib (an ATP-competitive inhibitor), which is currently the frontlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 152 publications
(148 reference statements)
0
30
0
Order By: Relevance
“…However, resistance to imatinib drove to development of the second and third tyrosine kinase inhibitors (Ren, 2005;Tanaka and Kimura, 2008). Thus, alternative drugs have been developed to circumvent this resistance (De Martino et al 2011;Lamontanara et al 2013;Schenone et al 2011). In this respect, the compounds (1), (3) and (5) induced a significant accumulation of cell population in sub-G1 phase suggesting that these compounds were able to promote apoptosis in K562 cells, a multiple drug resistance cell line.…”
Section: Discussionmentioning
confidence: 97%
“…However, resistance to imatinib drove to development of the second and third tyrosine kinase inhibitors (Ren, 2005;Tanaka and Kimura, 2008). Thus, alternative drugs have been developed to circumvent this resistance (De Martino et al 2011;Lamontanara et al 2013;Schenone et al 2011). In this respect, the compounds (1), (3) and (5) induced a significant accumulation of cell population in sub-G1 phase suggesting that these compounds were able to promote apoptosis in K562 cells, a multiple drug resistance cell line.…”
Section: Discussionmentioning
confidence: 97%
“…3,16,17 This mutant is not effectively targeted by any of the second-generation Imatinib derivatives, such as dasatinib, nilotinib, bosutinib and INNO-406. 7,18 Mass spectrometry analysis has revealed that, contrary to other mutations such as Y253H and E255V, the T315I substitution induces conformational changes in the Abl structure, particularly in the active site region (aminoacids 287-302) and in the SH3 linker domain.…”
Section: Discussionmentioning
confidence: 98%
“…A reciprocal translocation fuses the Abl gene on chromosome 9 with the breakpoint cluster region (Bcr) gene on chromosome 22. This fusion forms the Philadelphia (Ph) chromosome that generates a fusion protein, Bcr Abelson TK (Bcr-Abl), which possesses the TK activity of Abl and is constitutively active.…”
Section: Bcr-abl Tk and Chronic Myeloid Leukemiamentioning
confidence: 99%